MANAJEMEN PENINGKATAN MUTU TENAGA PENDIDIK DI MADRASAH IBTIDAIYAH AL YUSUFIAH KECAMATAN RANTAU SELATAN - Mansur Keling; Suwandi Suwandi; Maraya Monang Hasibuan (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to determine the implementation of the Quality Improvement Plan for Educators at Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District.Â This study uses a qualitative method, because it intends to explain the behavior of teachers and students in learning through the play model. While the data collection is using interview techniques, observation and documentation. Then to analyze the data is done by data reduction process, data exposure and drawing conclusions. To ensure the validity of the data, triangulation was carried out between methods, both interview data with observation, and documentation, as well as triangulation between informants.The results of this study that the implementation of the plan to improve the quality of educators in Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District has not fully followed the stages of implementing the general guidelines for implementation, because the concepts and objectives of the policy have not been fully understood by policy actors as a result of the implementation of policy socialization which is considered to be less than the maximum of courage and reactivity carried out by both the principal and teachers or educators at Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District. Supervision of Quality Improvement of Educators at Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District includes several stages, namely: supervision carried out at the beginning as a tool to anticipate or initial steps on the existence of obstacles and obstacles as well as deviations from the standards and objectives that have been prepared as well as a correction tool before a program is completed. Supervision during activities is a process carried out by prioritizing considerations.